Somatosensory Misrepresentation Associated with Chronic Pain: Spatiotemporal Correlates of Sensory Perception in a Patient following a Complex Regional Pain Syndrome Spread - Büntjen, Lars; Hopf, Jens-Max; Merkel, Christian; Voges, Jürgen; Knape, Stefan; Heinze, Hans-Jochen; Schoenfeld, Mircea Ariel (Frontiers in Neurology, 2017)
Chronic pain is suggested to be linked to reorganization processes in the sensorymotor cortex. In the current study the somatosensory representation of the extremities was investigated in a patient with a complex regional pain syndrome (CRPS) that initially occurred in the right hand and arm and spread later into the left hand and right leg. After the spread MEG recordings in conjunction with somatosensory stimulation revealed that the clinical symptoms were associated with major changes in the primary somatosensory representation. Stimulation of body parts triggering CRPS-related pain elicited activity located in the left primary somatosensory region corresponding to the right hand representation, where the CRPS initially appeared. Solely the unaffected left foot was observed to have a regular S1 representation. The pain distribution pattern was matching the cortical somatosensory misrepresentation suggesting that cortical reorganization processes might contribute and possibly underlie the development and spread of the complex regional pain syndrome.